THE BEST WAY TO IMPROVE SPEAKING SKILLS IN ENGLISH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Instead of translating from your native language, try thinking in English. This helps to build fluency and reduces hesitation. The most effective way to improve is by practicing with others. Find conversation partners, join English-speaking groups, or use language exchange apps. Many English words are built from common Latin or Greek roots. By learning the roots, prefixes, and suffixes, you can guess the meaning of new words more easily. For example, knowing that “bio” means life can help you understand words like “biology” and “biography.”